2005
DOI: 10.1088/0022-3727/38/23/004
|View full text |Cite
|
Sign up to set email alerts
|

Removal of formaldehyde from gas streams via packed-bed dielectric barrier discharge plasmas

Abstract: Formaldehyde is a major indoor air pollutant and can cause serious health disorders in residents. This work reports the removal of formaldehyde from gas streams via alumina-pellet-filled dielectric barrier discharge plasmas at atmospheric pressure and 70 °C. With a feed gas mixture of 140 ppm HCHO, 21.0% O2, 1.0% H2O in N2, ∼92% of formaldehyde can be effectively destructed at GHSV (gas flow volume per hour per discharge volume) of 16 500 h−1 and Ein = 108 J l−1. An increase in the specific surface area of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 32 publications
(28 reference statements)
1
53
0
Order By: Relevance
“…This shows that, in terms of pollutant conversion, the addition of oxygen is not necessary. Other authors have already obtained similar results: Ding et al8 showed that, for a given energy density, a variation of the oxygen content between 0 and 20% had no influence on the removal efficiency of formaldehyde.…”
Section: Resultssupporting
confidence: 58%
“…This shows that, in terms of pollutant conversion, the addition of oxygen is not necessary. Other authors have already obtained similar results: Ding et al8 showed that, for a given energy density, a variation of the oxygen content between 0 and 20% had no influence on the removal efficiency of formaldehyde.…”
Section: Resultssupporting
confidence: 58%
“…[8][9][10][11][12][13][14] In contrast, there are few available papers about CO 2 splitting in ap acked-bed DBD reactor, [15,16] especially with regard to energye fficiency. It has been demonstrated already for other applications, such as the destruction of volatile organic compounds (VOC), that as o-called packed-bed DBD reactor yields higher conversions and energye fficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested in the context of VOCr emediation [11][12][13] that the positive effects of ap acking are the result of the local enhanced electric field and thus higher electron energiesn ear the contact points of the dielectric beads, which is caused by the polarizationo ft hese beads by the external electric field. In other words,t he applied electrical energy will be used more efficiently to induce chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The energy cost for sequential treatment of air containing 4.7 ppm benzene was 3.7 × 10 −3 kWh/m 3 while 99.8% CO2 selectivity was achieved. The catalytic effect of Ag to promote CO oxidation to CO2 and the strong adsorption of Ag with benzene through π-complexation are found to be responsible for this high selectivity [41]. The effect of different catalysts and reactor configurations on plasma catalytic oxidation of stored benzene was also investigated by the same group [42].…”
Section: Sequential Treatment (Adsorption Followed By Ntp Oxidation)mentioning
confidence: 99%